Hypertension Self-Management and Quality of Life Correlation - Sari, Citra Windani Mambang; Pahria, Tuti; Wardani, Siti Dahlia (Sekolah Tinggi Ilmu Kesehatan Kendal, 2024)
Hypertension is a non-communicable disease that is one of the main problems in Indonesia where every year it always increases and becomes a comorbidity. To prevent complications of hypertension, patients must apply self-management that can affect the quality of life of sufferers. This study aimed to identify the relationship of self-management in hypertensive patients. This study used a quantitative descriptive design with a sample of 166 respondents through a non-probability sampling technique of total sampling type. The data collection technique used the Hypertension Self-management Behavior Questionnaire (HSMBQ) questionnaire. The data were analyzed using Pearson correlation. The results showed that in general, self-management of hypertension in general classified as poor (89%) including diet management (51.8%), weight control (54.8%), physical activity management (60.8%), poor stress management (62%), blood pressure monitoring (76%), and irregular hypertension treatment (77.8%). There are significant correlations between self-management and quality of life. Based on these results, it is important for primary health care and health workers to educate, evaluate and monitor the management carried out by hypertensive patients to improve hypertension self-management.